1996
DOI: 10.1002/bjs.1800830815
|View full text |Cite
|
Sign up to set email alerts
|

Wound metastases following laparoscopic and open surgery for abdominal cancer in a rat model

Abstract: The recent application of laparoscopic resection techniques to malignant disease has raised safety concerns due to metastasis to surgical access wounds. The significance and incidence of this problem are controversial. In the present study a rat model, in which an implanted tumour was lacerated, was used to investigate whether application of laparoscopic techniques for malignant abdominal disease leads to an increased risk of tumour dissemination and implantation within the peritoneal cavity, and abdominal wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
3
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 15 publications
3
101
3
1
Order By: Relevance
“…We have recently reported the results of a study on the impact of CO 2 and gasless laparoscopy on abdominal wall metastases in rats [4]. In accordance with the study by Watson and Mathew we found significantly greater port site metastases in rats having CO 2 laparoscopy compared to gasless laparoscopy [6]. Therefore, further study on gasless laparoscopy in digestive cancer is required.…”
supporting
confidence: 82%
“…We have recently reported the results of a study on the impact of CO 2 and gasless laparoscopy on abdominal wall metastases in rats [4]. In accordance with the study by Watson and Mathew we found significantly greater port site metastases in rats having CO 2 laparoscopy compared to gasless laparoscopy [6]. Therefore, further study on gasless laparoscopy in digestive cancer is required.…”
supporting
confidence: 82%
“…Laparoscopy also has been proposed in the staging of advanced ovarian cancer 8 or for second look procedures. Potential deleterious effects of CO 2 pneumoperitoneum have been described recently 1,2 . However previous studies have focused on port-site metastasis and peritoneal cell seeding, whereas general effects have not been investigated as much.…”
Section: Discussionmentioning
confidence: 99%
“…148,149 Several animal studies show that the effects of pneumoperitoneum, especially with carbon dioxide, lead to increased implantation of tumor cells in the abdominal wall. 12,150,151 Studies of rats undergoing laparoscopic surgery showed a threefold to fivefold increase in the incidence of metastases in the abdominal access wounds of those with pneumoperitoneum compared with those without pneumoperitoneum. 12,151 Some surgeons have proposed gasless laparoscopy to alleviate the theoretical concerns of pneumoperitoneum in cancer patients.…”
Section: Ca-a Cancer Journal For Cliniciansmentioning
confidence: 99%
“…12,150,151 Studies of rats undergoing laparoscopic surgery showed a threefold to fivefold increase in the incidence of metastases in the abdominal access wounds of those with pneumoperitoneum compared with those without pneumoperitoneum. 12,151 Some surgeons have proposed gasless laparoscopy to alleviate the theoretical concerns of pneumoperitoneum in cancer patients. 152,153 An added benefit of gasless laparoscopy is that conventional instruments can be used through the small incisions, potentially decreasing operative time.…”
Section: Ca-a Cancer Journal For Cliniciansmentioning
confidence: 99%